2020
DOI: 10.3390/jcm9123866
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Primary Tumor Location in Upper Tract Urothelial Carcinoma Treated with Nephroureterectomy: A Retrospective, Multi-Center Cohort Study in Taiwan

Abstract: We sought to examine the effect of tumor location on the prognosis of patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU). This retrospective study came from the Taiwan UTUC Collaboration Group, which consisted of 2658 patients at 15 institutions in Taiwan from 1988 to 2019. Patients with kidney-sparing management, both renal pelvic and ureteral tumors, as well as patients lacking complete data were excluded; the remaining 1436 patients were divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Unlike Western populations [3], the gender distribution of UTUC patients in Taiwan is dominated by women. A multicenter cohort study of 1436 patients from 15 institutions in Taiwan showed that 58% were female [4]. Currently, radical nephroureterectomy with bladder cuff excision remains the gold standard for the treatment of high-risk UTUC [5].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Western populations [3], the gender distribution of UTUC patients in Taiwan is dominated by women. A multicenter cohort study of 1436 patients from 15 institutions in Taiwan showed that 58% were female [4]. Currently, radical nephroureterectomy with bladder cuff excision remains the gold standard for the treatment of high-risk UTUC [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to identify prognostic factors in patients with UTUC [3][4][5][6]. These models are based on age, tumor grade, pathologic tumor grade, lymph node metastasis, lymphovascular invasion, tumor multifocality, and tumor architecture [3][4][5][6]. With the development of current genomics studies of UTUC [7], physicians can integrate the clinical pathologic characteristics with genetic and molecular subtyping of UTUC.…”
Section: Introductionmentioning
confidence: 99%
“…The current standard treatment for high-risk lesions is radical nephroureterectomy (RNU). However, disease recurrence or metastasis occurs in approximately 20–30% of patients 3 5 . Hence, to provide patients with better management options, a more precise and comprehensive UTUC assessment is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of RPTs seem to be higher 3 , 6 , 7 than that of UTs and RPTs often present a more advanced disease stage at the time of diagnosis 6 , 7 . Conversely, UTs are more likely to be organ-confined and have a greater association with bladder tumor history or recurrence 5 , 7 . Whether the prognosis of the two tumors is different has therefore been a matter of debate, but recent studies agree that RPTs are associated with better outcomes 3 , 5 , 6 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation